Optimizing Economic Development Through the Synergistic Influence of Information Technology on Educational Access and Human Capital Quality Enhancement - Teguh Santosa; Lili Fadli Muhamad (Jurnal Minfo Polgan, 2023)
This research aims to provide a deeper insight into the potential synergy between information technology, educational access, and the enhancement of human capital quality in the context of economic development. The research employs a comprehensive examination of available literature using qualitative analysis to gain a thorough understanding of the topic, encompassing the timeframe from 2015 to 2023. The study's findings indicate that optimizing economic development through the synergy of information technology, educational access, and the enhancement of human capital quality is a fundamental and relevant paradigm in addressing the challenges and opportunities of the globalization era. The integration of information technology into the education sector provides broader and more equitable access, while the improvement of human capital quality through technology establishes a strong foundation for sustainable economic growth.